Desenvolvimento rural sustentável: o caso do Programa de Aquisição de Alimentos (PAA) no território da cidadania Vales do Curu e Aracatiaçu-Ce - Holanda, Diego Rodrigues (2012)
The creation of the Territory of Citizenship of Valleys Curu and Aracatiaçu – CE as way to the sustainable rural development, through the Food Purchase Program (PAA) appears as the subject of research of great importance, for verifying the results obtained over the last years in terms of access to food in quantity, quality and regularity appropriate, and also in terms of measuring the strategic stocks needed to serve the population of the Territory of Citizenship object of this research. The aim of this work is to analyze the Food Purchase Program (PAA) as way a of sustainable rural development within the Territory of Citizenship in Curu and Aracatiaçu’s Valleys. To achieve the objectives of this study were used both primary data obtained through interviews and workshops with the individuals involved, and secondary data that were collected by the state government statistical sources (IPECE), IBGE and Ministry of Agrarian Development (SDA) with respect to data from the PAA. It was found that the Food Purchase Program (PAA) can be presented as a way for sustainable rural development for the municipalities themselves. For the territory, can not be presented due to lack of interaction between the municipalities. Altthough the contribution of the PAA for family farmers and coordination achieved between production and consumption beyond the attainment of the best market prices, the program complains that some weakness must be overcome. The exhaustive knowledge of such weakness can be instrumental in seeking and improvement in performance of the PAA.